Reasons behind net asset value deviations of listed UK property companies : Firm-specific variables explaining NAV discounts and premiums - Haapalainen, Mikko (My University, 2020)
The efficient market hypothesis states that the price of an asset should be equal to its fundamental value, which is the present value of future expected cash flows under conditions of currently available information. However, the efficient market hypothesis does not seem to be valid for listed property companies as the distinctive divergence between market capitalization and net asset value (NAV) of listed property companies is nowadays a widely recognized phenomenon in a field of real estate research. As the differences of NAV deviation have been significant between real estate companies within a relatively small market area, this indicates that equity markets are rewarding and punishing certain types of companies. The aim of this research is to analyze the driving firm-specific variables causing the difference between market capitalization and net asset value in listed property companies. Based on the data from the UK-listed real estate sector during 2000–2017, nine firm-specific variables are included in two different type of regression models. As previous research explaining the divergence in listed property companies is quite limited, this study especially focuses on strengthening earlier views and bringing out some new insights into NAV deviation. Parallel to previous NAV deviation studies conducted internationally, the results of this research present a clear correlation between some firm-specific factors and NAV deviation but also that companies tend to be valued in public markets relatively close to their NAVs. This study finds that higher dividend yield, property type diversification, liquidity spread, total assets as well as REIT status are positively related to the NAV discounts, which means that this kind of companies tend be valued under their NAVs. Thus, it could be reasonable, with certain qualifications, to sell or short sell companies that fulfill these criteria if the market has priced them above the NAVs. The results also show that higher total return, leverage ratio and a surprisingly an expense ratio are positively correlated to the NAV premium, which means that market is generally pricing these companies above their NAVs. Thus, it could be reasonable to buy companies fulfilling these criteria if the companies are trading at discount to their NAVs. These findings are also noteworthy for companies to maximize share value and minimize the risk of aggressive takeovers.

Tehokkaiden markkinoiden hypoteesin mukaan omaisuuslajin hinnan tulisi olla yhtä suuri kuin sen fundamenttiarvon, joka voidaan määritellä tulevien odotettujen kassavirtojen nykyarvoksi sen hetkisen tiedon valossa. Tehokkaiden markkinoiden hypoteesi ei kuitenkaan näytä pätevän listattujen kiinteistösijoitusyhtiöiden osalta, sillä näiden markkina-arvojen ja nettovarallisuuden välinen ero on nykypäivänä yleisesti tunnustettu ilmiö kiinteistöalalla. Koska markkinat ovat historiallisesti osoittaneet huomattaviakin arvostuseroja eri kiintestösijoitusyhtiöiden välillä, viittaa tämä siihen, että pääomamarkkinat arvostavat eri tavalla tietyntyyppisiä listattuja kiinteistösijoitusyhtiöitä. Tämän tutkimuksen tavoitteena on analysoida yrityskohtaisia muuttujia, jotka aiheuttavat listatuissa kiinteistösijoitusyhtiöissä eron nettovarallisuuden ja markkina-arvon välillä. Tutkimuksen datana on käytetty Lontoon pörssin kiinteistösijoitusyhtiöitä, joita tutkitaan yhdeksän eri muuttujan kautta kahdella eri regressiomallilla. Tässä tutkimuksessa keskitytään erityisesti suhteellisen vähäisten aikaisempien tutkimustulosten vahvistamiseen sekä samalla nostaen esille uusia näkökulmia ja mahdollisia vaikuttavia muuttujia. Aiempien tutkimusten mukaisesti myös tämän tutkimuksen tulokset osoittavat selkeän korrelaation tiettyjen muuttujien ja nettovarallisuuden poikkeamien välillä sekä markkina-arvojen ja nettovarallisuuden läheisen arvostuksen pitkällä juoksulla. Tuloksista käy ilmi, että korkean osinkotuoton, suuren taseen loppusumman, heikon likviditeetin, laajan kiinteistötyyppihajautuksen sekä REIT-yhtiömuodon omaavat yhtiöt korreloivat positiivisesti substanssialennuksen kanssa, jolloin yhtiö on arvostettu pörssissä alle oman nettovarallisuuden. Toisin sanoen tämä tarkoittaa, että edellä mainitut kriteerit täyttäviä yhtiöitä kannattaisi myydä tai lyhyeksi-myydä niiden ollessa arvostettu yli nettovarallisuutensa, sillä tilastollisesti tarkasteltuna nämä yhtiöt ovat yleisesti olleet hinnoiteltu alle nettovarallisuutensa. Tuloksista käy myös ilmi, että korkeampi historiallinen tuotto, velkaantuneisuus sekä hieman yllättäen kulurakenne korreloivat positiivisesti nettovarallisuuden yliarvostamisen kanssa. Nämä kriteerit täyttäviä yhtiöitä kannattaisi siis ostaa niiden ollessa hinnoiteltuna alle nettovarallisuutensa, sillä historiallisesti nämä yhtöt ovat olleet arvostettu yli nettovarallisuutensa. Tulokset ovat myös huomion arvoisia kiinteistösijoitusyhtiöille niiden pyrkiessään maksimoimaan osakkeenomistajien arvoa ja minimoimaan riskiä joutua aggressiivisten yrityskauppojen kohteeksi.
Keywords: Real estate, property, listed real estate, REIT, net asset value, NAV